Floristic Study of Shivaji Udyan from Jalgaon City of Maharashtra (International Journal of Scientific Research in Science and Technology, 2025)
Home-gardens of India are diverse and species rich. The history of gardens in India is as old as its civilization. The Aryans of the Vedic period were the great lovers of tree and flowers. The association of different trees with life of lord Buddha, emperor Asoka Lord Krishna and several Mughal emperor is well known, however importance of gardening is not understood well in India, therefore present investigation is undertaken. Several visits are made to the Shivaji Udyan. It is situated at the bank of Mehrun Lake to the western side of Jalgaon city, Maharashtra having area of 188460 sq.m areas. It is one of the oldest and largest garden in the city .Diversity of plants with local uses were analyzed. Although, 64 plant species representing 55 Genera belonging to 32 families and 3142 individuals were encountered. Various ornamental, edible, as well as plants of medicinal values are present in garden. Morinda citrifolia L, Santalum album L., Pterocarpous marsupium, Putranjiva roxburghii endangered species, were reported from the garden. Trees are dominant in the garden of which Polyalthia longifolia (sonner).Thw BL, Cassia siamea Lamk., Eucalyptus globules L., Cassia fistula L. are present in abundance. The high floristic diversity and presence of many species in the garden reflects the ways how to utilize and conserve plant diversity. Therefore, studies on floristic diversity of endangered species in cultivated gardens are required. So that potential of gardens for their conservation can be assessed.